Ukuran Perusahaan Memoderasi dampak Profitabilitas dan Intensitas Modal terhadap Penghindaran Pajak - Alun, Jervic Kristian; Louw, Febriana (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The purpose of this study is to examine the impact of profitability and capital intensity on tax avoidance, with company size serving as a moderating variable. The population and sample in this study are companies in the Consumer Non-Cyclical sector traded on the Indonesia Stock Exchange with a research period of 2020-2024. This study uses a quantitative approach with secondary data analysis methods from the official website of the IDX, with a purposive sampling technique. The research sample consists of 37 companies for the 2020-2024 period listed on the IDX. The data analysis used is descriptive statistics, classical assumption tests, multiple regression analysis, and moderation regression analysis. The analysis results show that profitability has a negative effect on tax avoidance, while capital intensity has a positive and significant effect on tax avoidance. The MRA test results show that the company size variable does not moderate the effect of profitability and capital intensity on tax avoidance.